Unethical Use of Information Technology in Higher Educational Institutions: A Case Study of a Faith-Based University in Ghana - Paul Adjei Onyina; Richard Afedzie (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2023)
Background: This study examined the unethical use of information technology among students in a Faith-based higher educational institution in Ghana. The choice of a Faith-based higher-level institution was based on the moral values and strict religious code of conduct inscribed in the culture of the university. Methods: A cross-sectional primary data used for analysis was gathered from June to July 2021. The choice of a cross-sectional was to compare the perspectives of the gender, age groups, and economic levels among various students in the university. A structured questionnaire was provided online for students willing to participate in the study to complete and submit online. A sample size of 574 students answered the closed ended online questionnaire for data analysis. Gender and education level were used to assess the primary reasons for the unethical use of information technology by students. SPSS software version 21 was used for data analysis.Results: Students who participated in the study were 239 males (42.5) and 324 females (57.5). Among some of the reasons for unethical behavior was easier access to information technology which enabled the students to engage in wrong activities (mean score 3.11, standard deviation 1.154). Students with financial support were less likely not to be involved in IT to perform well (mean score 3.00, standard deviation 1.169). The students working and studying at the same time had less time to study and resorted to unethical use of IT (mean score 3.26, standard deviation1.050). Conclusion: This study recommends that universities should teach ethics of information technology as a stand-alone course, and that higher-level institutions should periodically present academic seminars on unethical use of information technology.